Actual Problems of Administrative Responsibility for Admission to Drivinga Person Who Is Under the Influence of Alcohol or Who Does Not Have the Right to Drive a Vehicle - Arina V. Kuyanova (Сибирское юридическое обозрение, 2017)
The subject of the study are the norms of the Code of the Russian Federation on Administrative Offenses providing for the grounds and procedure for bringing to administrative responsibility of officials and legal entities for admission of a person to driving who is under the influence of alcohol or who does not have the right to drive a vehicle. The object of the study is public relations, developing in the field of road safety. The Author, in the framework of the article, pays attention to the peculiarities of regulation of the public relations under consideration by by-laws; problems of law application practice; explanations of the judicial authorities that allow to unify the practice of resolving the relevant category of cases, to ensure the most effective protection of the rights and legitimate interests of society and the state in the field of road safety. Proposals specifying certain provisions of the Code of the Russian Federation on Administrative Offenses are formulated.